Experimental Study on the Out-of-Plane Behavior of Brick Masonry Walls Strengthened with Mortar and Wire Mesh: A Pioneer Study - Panuwat Joyklad (MDPI AG, 2021)
In the past, fiber-reinforced polymer (FRP) composites have been extensively used to modify the structural response of masonry brick walls. The promising advantages of FRP composites are easy application, lightweight, and very high tensile strength. However, FRP composites are very expensive, and their availability is an issue, especially in developing countries. The use of bricks is widespread in developing countries due to their low price and easy availability. Recent earthquakes and research results have demonstrated the vulnerability of existing masonry structures. In this study, we aimed to investigate the use of low-cost and readily available strengthening materials, i.e., cement-sand mortar and wire mesh, to enhance the flexural capacity of cement-clay interlocking brick (CCIB) masonry walls. The proposed strengthening materials were applied in different configurations and thicknesses. The experimental results indicated that using CS mortar and wire mesh is promising to enhance the flexural capacity of CCIB masonry walls. The flexural capacity and energy absorption capacity of the CCIB masonry wall (strengthened with 20 mm thick CS mortar and three layers of wire mesh) were 87% and 46% higher than the reference CCIB masonry wall. The results of this study can be used to improve the performance of masonry structures against earthquakes in the developing regions.